Evaluasi dan Perbaikan Desain Antarmuka Pengguna Website Dinas Kesehatan Kabupaten Kediri menggunakan Metode Human Centered Design - Andreas Kurnia Ferdiantoro; Retno Indah Rokhmawati; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The Kediri District Health Office uses the website as a medium to deliver health information to the people living in Kediri Regency and as a staffing information center for all parties related to health. From the interviews found a problem. users have difficulty finding information on the website. This is because the website does not involve the user in its development. In addition, the website has not been updated in terms of interface since 2014. So an evaluation with the Human Centered Design approach is needed to improve the website usability. This study has 4 stages: determining the user context, specifying user needs, generating design solutions and evaluating designs. This study uses testing by interviewing 6 users of the Kediri District Health Office website to explore problems and get improvement input. In addition this study also uses testing with the SUS questionnaire given to 20 respondents to get the usability value. From the initial evaluation results obtained an analysis of the problems and proposals that are used as a reference for improvement on the website Improvements made in terms of color selection, adding new pages, providing navigation instructions page and eliminating breadcrumb navigation. From the final evaluation the improvement resulted in the value of the SUS questionnaire at 80.25. These results are supported by positive responses from the results of user interviews, the majority of which said the website was easier to use..